2016
DOI: 10.1177/1087057116650402
|View full text |Cite
|
Sign up to set email alerts
|

FRET-Protease-Coupled Peptidyl-Prolyl cis-trans Isomerase Assay

Abstract: In this work, a sensitive and convenient protease-based fluorimetric high-throughput screening (HTS) assay for determining peptidyl-prolyl cis-trans isomerase activity was developed. The assay was based on a new intramolecularly quenched substrate, whose fluorescence and structural properties were examined together with kinetic constants and the effects of solvents on its isomerization process. Pilot screens performed using the Library of Pharmacologically Active Compounds (LOPAC) and cyclophilin A (CypA), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…We have tested this hypothesis using a CypA peptide substrate 25 and performing binding experiments between wild type and R55A mutant protein and the substrate in the presence and absence of the AIF(370-394) and CsA. Data showed that, in line with the large difference in affinity (57 nM for the substrate and 6 μM for the AIF peptide), AIF(370-394), used at a 10-fold excess, is unable to prevent the binding of both CypA and CypA R55A to the substrate, but recognition is abolished in the presence of the strong inhibitor CsA (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have tested this hypothesis using a CypA peptide substrate 25 and performing binding experiments between wild type and R55A mutant protein and the substrate in the presence and absence of the AIF(370-394) and CsA. Data showed that, in line with the large difference in affinity (57 nM for the substrate and 6 μM for the AIF peptide), AIF(370-394), used at a 10-fold excess, is unable to prevent the binding of both CypA and CypA R55A to the substrate, but recognition is abolished in the presence of the strong inhibitor CsA (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…His-tagged CypA (hereafter CypA) and the corresponding R55A mutant, were expressed and purified as previously reported 25 . The protein concentration was determined by reading the absorbance at 280 nm with a NanoDrop200c UV-Vis spectrophotometer and using a theoretical molar extinction coefficient of 8730 M −1 cm −1 .…”
Section: Methodsmentioning
confidence: 99%